Por escolas ribeirinhas que valorizem os saberes e o protagonismo das mulheres pescadoras na RDS Vitória de Souzel, Senador José Porfírio, Pará - SOUSA, Edileusa da Silva (2023)
The aim was to reflect on how the knowledge of fishing and traditional fisherwomen can be approached in riverside schools, with a view to problematizing the socio-environmental reality and the relationship with the ways of life of the population of the Vitória de Souzel Sustainable Development Reserve, in Senador José Porfírio, Pará. The methodology was qualitative, based on data generated through semi-structured interviews with four artisanal fisherwomen. The data shows that women fishermen have knowledge about fishing that they have accumulated through their daily experiences, as well as representing ways of relating to and interpreting nature, understood through observation and the teachings of more experienced generations. They also feel the need for artisanal fishing to be valued in the school environment where their children study.